Assessment of myofibroblast activity at the stages of surgical treatment of wound defects in complicated forms of chronic venous insufficiency - S.I. Savoliuk; A.R. Dembitskyi; I.M. Shmyhina (Медицина неотложных состояний)
Background. The purpose of the study was to evaluate the healing potential of trophic ulcers (TUs) in patients with chronic venous insufficiency (CVI) C6 by analyzing the expression of the -SMA marker as a prognostic indicator of treatment effectiveness using platelet-rich plasma (PRP), in comparison with traditional TU treatment methods. Materials and methods. The study conduc-ted in 2021–2023 involved 33 patients divided into the main (n = 15) and the control groups (n = 18). The main group underwent thermal ablation of the saphenous vein trunks and local treatment of TUs with PRP. In the control group, stripping of the incompetent trunks was performed using traditional local treatment for TUs (ointments, dressings). Treatment effectiveness was evaluated based on clinical parameters, TU healing time, and -SMA expression in tissue samples. Results. The use of PRP promoted faster epithelialization of TUs, reduced inflammatory markers, and increased -SMA expression. This indicates myofibroblast activation, which is associated with accelerated wound healing. Compared to traditional treatment methods, the use of PRP in the TU area proved to be more effective and resulted in a significant reduction in TU healing time. The application of PRP combined with modern wound dressings allowed to achieve TU healing in CVI C6 patients by day 32.9 (p-value = 1.044e-10), whereas in the comparison group, TU hea-ling was observed by day 52.7 (p-value = 1.044e-10). Conclusions. The results of the study confirm the effectiveness of PRP injections in combination with modern wound dressings to accelerate the healing of trophic ulcers in patients with CVI C6.